THE USE OF FLIPPED CLASSROOM MODEL IN READING COMPREHENSION - Rizal Fahmi; Lilies youlia Friatin; Leni Irianti (JALL (Journal of Applied Linguistics and Literacy), 2020)
This study presents the use of the flipped classroom model in reading comprehension. This study is aimed to investigate the teacher’s way of implementing flipped classroom in teaching reading narrative text and reveal students’ perception toward the teaching model. A qualitative case study was applied as the research design of this study. The subject of this study was chosen purposively, consisting of twenty-three students from the tenth grade (X AK-1) and one English teacher in one of the vocational high schools in Cilacap, Indonesia. The writers applied the triangulation technique as where the data were analyzed through multiple resources to get more reliable data. The result of the study was showed that the teacher implemented four main stages in teaching reading narrative text using the flipped classroom model. Meanwhile, regarding the students’ perception, students perceived all the stages and activities in the flipped classroom model positively. The students viewed that flipped classroom as a fun learning model, which helped them became a more active learners, and help them overcome their shortcomings. Finally, other researchers are suggested to explore deeply into the implementation of the model that targets other topics and skills, apply other framework suggested by other experts, and explore the students’ perception using an open questionnaire to reveal the reason underlying the perception.Keywords: Flipped Classroom, Teaching Reading, Narrative Text